Experimental airborne transmission of Salmonella Agona and Salmonella Typhimurium in weaned pigs - Oliveira, CJB; Carvalho, LFOS; Garcia, T. B. (Cambridge University Press, 2006)
This study tested the hypothesis of airborne transmission of Salmonella Agona (Trial I) and Salmonella Typhimurium (Trial II) in weaned pigs. The trials were performed using stainless-steel/glass isolation cabinets connected by air ducts to permit an unidirectional airflow from cabinet 1 (two control pigs) to cabinet 3 (two sentinel pigs), passing through cabinet 2 (two inoculated pigs). Air samples, pooled faecal samples from the floor and rectal swabs were collected daily and assessed by culture and PCR. A fumigation chamber and rubber gloves coupled to the cabinets allowed sampling without opening the system. Trials I and II lasted 15 and 19 days respectively. The recovery of S. Agona and S. Typhimurium and detection of scroconversion in sentinel pigs indicate that airborne Salmonella transmission in weaned pigs over short distances is possible. Further studies on the role of aerosols in the epidemiology of Salmonella in intensive pig production should be performed.